A porous carbon and a method for preparing the same

CN123002823APending Publication Date: 2026-10-30HAIKE GRP RES INST OF INNOVATION & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611485976.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-23
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

其虽进行了硫元素回收以及制备了高微孔率的多孔碳,但同样地,该类型多孔碳无内外分级,单一性的微孔碳只适合极低硅负载的场景,一旦追求高硅含量,会出现严重表面堵孔、硅层剥落,循环寿命差

Benefits of technology

本发明提供了一种多孔碳的制备方法,通过W1/O/W2型双重乳液体系,以低浓度的钾盐活化剂水溶液W1为内水相W1、高浓度的钾盐活化剂水溶液W2为外水相,实现了钾盐活化剂在生焦中“外层富钾、内层贫钾”的梯度分布,突破了传统物理混合法难以实现活化剂空间分布调控的技术瓶颈;内层贫钾区域在碳化过程中保留微孔结构,外层富钾区域通过活化反应形成介孔外壳,一步法制备了外介孔-内微孔的梯度结构多孔碳;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123002823A_ABST
    Figure CN123002823A_ABST
Patent Text Reader

Abstract

The application discloses a kind of porous carbon and preparation method thereof, belong to carbon material preparation technical field.Its technical scheme includes the following steps: to raw oil slurry, add lipophilic surfactant, stir, obtain pretreatment material;Low concentration of potassium salt activator aqueous solution is slowly added in pretreatment material, under high-speed shearing, form W1 / O primary emulsion;W1 / O primary emulsion is added to high concentration potassium salt activator aqueous solution containing hydrophilic surfactant under stirring, and stable W1 / O / W2 double emulsion is formed by high-speed homogenization;Double emulsion is freeze-dried, coking-carbonization treatment and pickling, washing, drying, and porous carbon product is obtained.The application provides a kind of preparation method of porous carbon, through double emulsion system, inner layer poor potassium area retains microporous structure in carbonization process, outer layer rich potassium area is formed mesoporous shell by activation reaction, and gradient structure porous carbon of outer mesoporous-inner microporous is prepared by one-step method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of carbon material preparation technology, and particularly relates to a porous carbon and its preparation method. Background Technology

[0002] Currently, petroleum coke, a low-cost, high-carbon solid byproduct of petroleum refining, is being transformed into a valuable resource, making its utilization a research hotspot in materials science. Through specific activation processes, petroleum coke can be converted into porous carbon materials with high specific surface area and high electrical conductivity, which have important applications in the field of supercapacitors.

[0003] Patent CN103641114A discloses a method for preparing porous activated carbon with an iodine adsorption value of 1000 mg / g and a methylene blue adsorption value of 800 mg / g by uniformly mixing petroleum coke with an activator (potassium hydroxide, zinc chloride, etc.) and a template agent, followed by tableting and high-temperature reaction under an inert atmosphere, acid washing, and drying. While high specific surface area activated carbon products can be prepared by physically mixing petroleum coke, template agents, and activators, the porous carbon prepared by this method lacks a clear internal and external pore structure, with micro, meso, and macroporous structures being randomly dispersed. Furthermore, the consumption of nano-template agents and activators is enormous, resulting in high costs; for example, the alkali-to-coke ratio (activator / petroleum coke) is as high as 7. Patent CN105712347B discloses a method for preparing sulfur-rich activated carbon using high-sulfur petroleum coke. The method involves mixing potassium hydroxide with 60-120 mesh high-sulfur petroleum coke in a 1:3-8 ratio, activating the mixture, and then treating it with acid to obtain sulfur-rich activated carbon. Sulfur is then recovered using an impregnation method, achieving "sulfur fixation and mercury removal," significantly reducing costs and pollution. While this method achieves sulfur recovery and prepares porous carbon with high microporosity, it lacks internal and external gradation. The single-layer microporous carbon is only suitable for scenarios with extremely low silicon loading. Pursuing high silicon content leads to severe surface clogging, silicon layer peeling, and poor cycle life.

[0004] In summary, current technologies for activating petroleum coke using alkaline activators such as KOH or NaOH often require high alkali concentrations, resulting in significant waste processing pressures. The high specific surface area porous carbon produced is often difficult to finely control in structure, hindering the synthesis of specialized structures. Furthermore, this type of carbon material exhibits poor adaptability to silicon volume expansion during charge-discharge processes. Additionally, systems using low amounts of alkaline activators often require additional activation conditions, such as water vapor or carbon dioxide. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a porous carbon and its preparation method. It utilizes a dual emulsion system to regulate the spatial distribution of potassium salts and to ensure that the thermal decomposition behavior of potassium salts is highly matched with the matrix polycondensation process. The decomposition products are then used to etch the carbon layer in a directional manner, thereby forming a porous carbon with an external mesopore-internal micropore gradient structure.

[0006] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: This invention provides a method for preparing porous carbon, comprising the following steps: 1) Add a lipophilic surfactant to the raw oil slurry, stir, and obtain the pretreated material; 2) Slowly add a 5%~10% potassium salt activator aqueous solution W1 to the pretreated material to form a W1 / O primary emulsion under high-speed shearing; 3) The W1 / O primary emulsion was added to an aqueous solution of potassium salt activator containing 20%~30% hydrophilic surfactant under stirring, and a stable W1 / O / W2 type double emulsion was formed by high-speed homogenization. 4) The W1 / O / W2 type dual emulsion was pre-frozen and then freeze-dried to obtain a carbon source precursor; 5) Under an inert atmosphere, coking-carbonization treatment is carried out to obtain carbonized samples; 6) The carbonized sample is sequentially acid-washed, water-washed, and dried to obtain a porous carbon product; In step 2), the rotational speed of the high-speed shear is 1.2 × 10⁻⁶. 4 ~2.0×10 4 rpm, time is 5~30 min; In step 3), the rotational speed for high-speed homogenization is 1.2 × 10⁻⁶. 4 ~2.0×10 4 rpm, time is 5~30 min.

[0007] Preferably, the volume ratio of potassium salt activator aqueous solution W1 to potassium salt activator aqueous solution W2 is 1:5 to 1:8; The volume ratio of potassium salt activator aqueous solution W1 to raw material oil slurry is 1:10~1:6.

[0008] Preferably, in steps 2) and 3), based on potassium salt solute, the potassium salt mass m1 in the potassium salt activator aqueous solution W1 is 0.5 wt% to 1.5 wt% of the raw material oil slurry mass, and the potassium salt mass m2 in the potassium salt activator aqueous solution W2 is 10 wt% to 24 wt% of the raw material oil slurry mass; m2 / m1 is 10 to 40, and m1+m2 is 10 wt% to 25 wt% of the raw material oil slurry mass.

[0009] Preferably, the potassium salt activator in steps 2) and 3) is selected from at least one of potassium hydroxide, potassium carbonate, potassium bicarbonate, potassium oxalate, potassium phosphate, potassium acetate, potassium citrate, potassium ethylenediaminetetraacetate, potassium stearate, and potassium tetraoxalate.

[0010] Preferably, in step 1), the feedstock slurry is at least one of catalytic cracking slurry, vacuum residue, coking wax oil, ethylene tar, and coal tar pitch.

[0011] Preferably, in step 1), the lipophilic surfactant is at least one of the Span series or polyglycerol ricinoleate, with a hydrophilic-lipophilic balance value of 3-6; the amount of lipophilic surfactant added is 1wt%~5wt% of the oil slurry mass. In step 3), the hydrophilic surfactant is at least one of the Tween series and sodium dodecyl sulfate, with a hydrophilic-lipophilic balance value (HLB) of 8 to 15; the amount of hydrophilic surfactant added is 0.5 wt% to 5 wt% of the mass of the potassium salt activator aqueous solution W2.

[0012] Preferably, in step 4), the pre-freezing temperature is -40℃ to -80℃ and the vacuum degree is 10 to 50 Pa.

[0013] Preferably, in step 5), the coking-carbonization process is as follows: the temperature is increased to 400~450℃ at a heating rate of 5℃ / min for coking for 1~2 hours, and then the temperature is increased to 700~900℃ at a heating rate of 5℃ / min for carbonization for 1~4 hours, and the whole process is carried out under an inert atmosphere. In step 6), the carbonized sample is uniformly dispersed in a pure aqueous solution and acid-washed with an acid washing solution to obtain a mixed solution; the mixed solution is filtered, washed with pure water, and then dried at 100~150℃ for 12~24h to obtain porous carbon. The pickling solution is at least one of hydrochloric acid and sulfuric acid, and the concentration of the pickling solution is 1 mol / L.

[0014] In another aspect, the present invention provides porous carbon prepared by the above preparation method. The porous carbon has a core-shell structure, with a core of micropores and a shell of mesopores, and a mesopore / micropore volume ratio of 0.2 to 0.8. Porous carbon with a specific surface area ≥1000 m² 2 / g, total pore volume ≥0.5 cm³ 3 / g.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention provides a method for preparing porous carbon. Using a W1 / O / W2 type dual emulsion system, with a low-concentration potassium salt activator aqueous solution W1 as the inner aqueous phase and a high-concentration potassium salt activator aqueous solution W2 as the outer aqueous phase, a gradient distribution of the potassium salt activator in the coke is achieved, characterized by a "potassium-rich outer layer and potassium-poor inner layer." This overcomes the technical bottleneck of traditional physical mixing methods, which struggle to control the spatial distribution of the activator. The potassium-poor inner region retains its microporous structure during carbonization, while the potassium-rich outer region forms a mesoporous shell through activation. This one-step method prepares porous carbon with a gradient structure of outer mesoporous and inner microporous layers. This invention utilizes the precise matching of the potassium salt thermal decomposition temperature and the carbonization temperature zone to enable the outer potassium salt to be directionally etched at high temperature to form a mesoporous shell, while the inner potassium-poor region retains the microporous core. This avoids the complex process of multi-step template methods, and the process is simple and cost-controllable. The porous carbon obtained in this invention has a gradient structure of external mesopores and internal micropores: the core micropores can provide a high specific surface area and abundant active sites, which is beneficial for anchoring silicon particles and inhibiting silicon pulverization during cycling; the outer shell mesopores construct a fast ion transport channel, which is beneficial for electrolyte wetting and buffering the volume expansion of silicon, thereby significantly improving the cycling stability of silicon-carbon anodes and having broad application prospects in the field of energy storage. Attached Figure Description

[0016] Figure 1 This is a scanning electron microscope image of the raw coke prepared in Example 1 of the present invention; wherein, Figure 1 Image (a) is a scanning electron microscope image of the internal cross-section of the forked area. Figure 1 (b) in the image is a scanning electron microscope image of the coked surface; Figure 2 This is a scanning electron microscope (SEM) image of the porous carbon prepared in Example 1 of the present invention; wherein, Figure 2 Image (a) is a low-magnification scanning electron microscope image of porous carbon. Figure 2 (b) is a high-magnification scanning electron microscope image of porous carbon; Figure 3 This is a TEM image of the porous carbon prepared in Example 1 of the present invention; Figure 4 The XRD pattern of the coke prepared in Example 1 of this invention; Figure 5 Here is a scanning electron microscope (SEM) image of the porous carbon prepared in Comparative Example 1 of this invention; wherein, Figure 5 (a) in the image is a scanning electron microscope image of a specific region of porous carbon; Figure 5 (b) is a scanning electron microscope image of another region of porous carbon; Figure 6 Here is a scanning electron microscope (SEM) image of the porous carbon prepared in Comparative Example 2 of this invention; wherein, Figure 6 Image (a) is a low-magnification scanning electron microscope image of porous carbon. Figure 6 (b) is a high-magnification scanning electron microscope image of porous carbon. Detailed Implementation

[0017] The technical solution of the present invention will now be described in detail and completely with reference to specific embodiments. Obviously, the described embodiments are merely some specific implementations of the overall technical solution of the present invention, and not all implementations. Based on the overall concept of the present invention, all other embodiments obtained by those skilled in the art fall within the protection scope of the present invention.

[0018] This invention provides a method for preparing in-situ pore-forming coke-based porous carbon based on thermal decomposition matching of potassium salts, comprising the following steps: 1) Add a lipophilic surfactant to the raw oil slurry, stir, and obtain the pretreated material; 2) Slowly add a 5%~10% potassium salt activator aqueous solution W1 to the pretreated material to form a W1 / O primary emulsion under high-speed shearing; 3) The W1 / O primary emulsion was added to an aqueous solution of potassium salt activator containing 20%~30% by mass of hydrophilic surfactant under stirring, and a stable W1 / O / W2 type double emulsion was formed by high-speed homogenization. 4) The W1 / O / W2 type dual emulsion was pre-frozen and then freeze-dried to obtain a carbon source precursor; 5) Under an inert atmosphere, coking-carbonization treatment is carried out to obtain carbonized samples; 6) The carbonized sample is sequentially acid-washed, water-washed, and dried to obtain a porous carbon product.

[0019] In this invention, a spatial gradient distribution of potassium salt activator in the oil phase is achieved through a W1 / O / W2 type dual emulsion system—the high-concentration potassium salt in the outer aqueous phase W2 is wrapped around the outermost layer of the emulsion, while the low-concentration potassium salt in the inner aqueous phase W1 is located in the innermost layer of the emulsion. After freeze-drying and coking processes, the oil phase gradually condenses and solidifies, forming a raw coke structure with a potassium-rich outer layer and a potassium-poor inner layer. In the subsequent carbonization and activation process, the high-concentration potassium salt in the outer layer undergoes a full activation reaction with the carbon matrix, forming a mesoporous outer shell through directional etching; while the potassium-poor inner layer has a weak activation degree, and in addition, some micropores can be formed by the condensation and carbonization of the raw oil slurry itself, forming a microporous core. Thus, a gradient pore structure is achieved where "the outer mesopores are dominated by potassium salt activation, while the inner micropores are retained due to potassium deficiency".

[0020] In this invention, the potassium salt activator is one or more of the following potassium salts: potassium hydroxide, potassium carbonate, potassium bicarbonate, potassium oxalate, potassium phosphate, potassium acetate, potassium citrate, potassium ethylenediaminetetraacetate, potassium stearate, and potassium tetraoxalate. These potassium salts do not react with the oil slurry during coking and can gradually decompose, thus not introducing additional heteroatom residues as potassium salt activators. The thermal decomposition behavior of different potassium salts varies: potassium bicarbonate, for example, begins to decompose into potassium carbonate at approximately 310°C; potassium carbonate has higher thermal stability and continues to provide activation at higher temperatures; the decomposition behavior of potassium oxalate and potassium tetraoxalate falls between the two. By selecting different potassium salts or using them in combination, the activation temperature zone can be controlled to match different carbonization heating programs, achieving a time-series matching of "activation as carbonization progresses." The total amount of potassium salt activator added is 10 wt%-25 wt% of the raw material oil slurry. If the amount added is less than 10 wt%, there will be insufficient activation sites for the outer potassium salt layer and the mesoporous shell will not develop sufficiently. If the amount added is more than 25 wt%, the gas produced by the decomposition of the activator will be excessive, resulting in the excessive expansion of mesopores into macropores and a decrease in microporosity.

[0021] In this invention, a low-concentration potassium salt activator aqueous solution W1 is first slowly added to the pretreated material, forming a W1 / O primary emulsion under high-speed shearing. Then, the W1 / O primary emulsion is added to a high-concentration potassium salt activator aqueous solution W2 containing a hydrophilic surfactant under stirring, and a stable W1 / O / W2 type dual emulsion is formed through high-speed homogenization. The core function of this feeding sequence is that the total potassium content in the inner aqueous phase W1 is low, ensuring that the inner layer of the coke is a potassium-deficient region; while the total potassium content in the outer aqueous phase W2 is high, ensuring that the outer layer of the coke is a potassium-rich region. Furthermore, by controlling the volume ratio of W1 to W2, the thickness of the mesoporous outer shell and the size of the microporous core can be further controlled. The volume ratio of the low-concentration potassium salt activator aqueous solution (W1) to the potassium salt activator aqueous solution (W2) is 1:5 to 1:8. If the W1 / W2 volume ratio is higher than 1:5, meaning the proportion of the outer water phase is too low, the activation dose of the outer potassium salt is insufficient, the mesoporous shell is not fully developed, and the resulting porous carbon has a mesoporous / microporous pore volume ratio of less than 0.2, making it impossible to form a continuous mesoporous shell structure. If the W1 / W2 volume ratio is lower than 1:8, meaning the proportion of the outer water phase is too high, the activation dose of the outer potassium salt is too large, the activation reaction is too violent, the outer mesopores are excessively expanded into macropores (>10 nm), and at the same time, the inner potassium-deficient region may be partially activated due to heat transfer, resulting in the destruction of the microporous core structure and a decrease in the proportion of micropores.

[0022] In this invention, the rotational speed for high-speed shearing and high-speed homogenization is 1.2 × 10⁻⁶. 4 ~2.0×10 4 Within this speed range, efficient shearing of the oil-water two-phase system can be achieved. If the speed is below 1.2 × 10 rpm... 4At speeds above 2.0 × 10⁻⁶ rpm, insufficient shear force prevents effective breakup of aqueous droplets. The W1 / O primary emulsion droplets are typically in the micrometer range (>1 μm). The resulting double emulsion droplets after secondary emulsification are larger and unevenly distributed. The potassium salt activator forms island-like clusters on the outer layer of the coke instead of a continuous and uniform distribution, failing to form a continuous and complete mesoporous shell after carbonization. 4 Excessive shear force at high rpm generates a large amount of heat, leading to localized overheating of the emulsion. This can cause demulsification or emulsifier failure, disrupting the dual emulsion structure, causing the internal and external aqueous phases to merge, and preventing the potassium salt activator from maintaining its gradient distribution. The time for high-speed shearing and high-speed homogenization is 5–30 min. If the time is too short, emulsification will be insufficient; if the time is too long, energy consumption will increase and the emulsion stability may be affected.

[0023] In this invention, the feedstock slurry is at least one of catalytic cracking slurry, vacuum residue, coking wax oil, ethylene tar, and coal tar pitch. Its most crucial feature lies in the precise matching of thermal polycondensation behavior and potassium salt thermal decomposition behavior within a specific temperature window: during the low-temperature coking stage (400~450℃), polycyclic aromatic hydrocarbon molecules in the feedstock undergo dehydrogenation polycondensation, forming a cross-linked network of polycyclic aromatic hydrocarbons connected by methylene bridges through random intermolecular collisions. This network ultimately solidifies into isotropic amorphous raw coke with disordered carbon layer arrangement and random layer stacking characteristics. Meanwhile, potassium salts have not yet undergone significant decomposition within this temperature range, but are uniformly enriched in ionic form on the outer layer of the raw coke, without interfering with the polycondensation process. This process preserves sufficient active species for subsequent activation. In the intermediate temperature stage (accompanied by the heating process until the early stage of carbonization), as the temperature rises, the potassium salts enriched in the outer layer begin to decompose gradually, releasing gases such as CO2. During the escape of these gases, gas etching channels are formed in the carbon skeleton, which preferentially attack the structural defects and edge sites that exist in the disordered carbon layers, causing the outer layer of the carbon skeleton to be directionally etched to form a mesoporous shell. In the high-temperature carbonization stage (700~900℃), the potassium vapor produced by the further decomposition of potassium salts is embedded between the carbon layers, playing an intercalation and expansion role. After the subsequent acid washing removes the embedded potassium elements and their compounds, a porous structure dominated by micropores is left in the carbon skeleton. The sequential synergy of three temperature stages—low-temperature cross-linking and carbon fixation, medium-temperature gas etching to form mesopores, and high-temperature potassium intercalation to form micropores—spatially separates the formation of mesopores (medium-temperature gas etching) from the formation of micropores (high-temperature potassium intercalation and removal). Mesopores are mainly distributed in the outer potassium-rich region, while micropores are mainly distributed in the inner potassium-poor region, ultimately achieving synchronous gradient pore formation "as carbonization and activation progress." Furthermore, the low heteroatom content of these raw materials avoids interference from oxygen / nitrogen-containing functional groups on the potassium salt activation reaction. Their non-polar characteristics and good compatibility with lipophilic surfactants are beneficial for the stable construction of the dual emulsion.

[0024] In this invention, the lipophilic surfactant is at least one of the Span series (such as Span 80) and polyglycerol ricinoleate (PGPR); the surfactant is a lipophilic surfactant with an HLB value of 3-6; the amount of surfactant added is 1 wt%-5 wt% of the oil slurry mass. If a single surfactant is used, a water-in-oil surfactant such as Span 80 (HLB=4.3) is used; if a compound surfactant is used, the HLB value of the compound is controlled between 3 and 6. When the HLB value of the surfactant is between 3 and 6, it is beneficial to form a stable water-in-oil emulsion. If the HLB value is below 3, the lipophilicity is too strong, and the emulsifying ability is insufficient; if the HLB value is above 6, it tends to form an oil-in-water emulsion, which is not conducive to the stability of the dual emulsion structure. When the amount of surfactant added is less than 1 wt%, a stable W1 / O primary emulsion cannot be formed, the aqueous phase droplets are prone to agglomeration, the droplet size increases and the distribution is uneven, and the pore structure of the porous carbon obtained after carbonization is uneven and the mesoporous shell is discontinuous. When the amount added is greater than 5 wt%, the excess surfactant remains in the carbon skeleton after pyrolysis during coking and carbonization, blocking some pores and causing a decrease in specific surface area and pore volume.

[0025] In this invention, the hydrophilic surfactant is at least one of the Tween series and sodium dodecyl sulfate, with a hydrophilic-lipophilic balance (HLB) of 8-15. The reason for adding it at 0.5wt%-5wt% of the mass of the potassium salt activator aqueous solution W2 is based on the mechanism requirement for the stability of the dual emulsion interface: in the W1 / O / W2 structure, the O / W interface between the external aqueous phase W2 and the oil phase requires a hydrophilic surfactant to reduce interfacial tension and form a stable hydration layer or electrostatic repulsion barrier, so that the W1 / O primary emulsion droplets can be uniformly dispersed in the high-concentration potassium salt external aqueous phase without aggregation; HLB 8-15 is the classic window for forming O / W type emulsions. Considering that high salt W2 will reduce the hydration degree of nonionic surfactant polyoxyethylene chains and decrease apparent HLB, this range balances salt resistance and effective emulsification ability. Tween series can still stabilize the interface in high salt environment through steric hindrance, while SDS assists dispersion through electrostatic repulsion. The two can be used alone or in combination to enhance the interfacial film strength. The lower limit of addition (0.5wt%) ensures sufficient molecular coverage of the outer interface, while the upper limit (5wt%) prevents excessive hydrophilic emulsifier from crossing the oil film to compete for the inner interface, destroy the W1 / O primary emulsion, or remain in the carbon precursor and introduce impurities. Thus, while ensuring the integrity of the dual emulsion structure, it provides a controllable precursor basis for subsequent freeze-drying to fix the potassium salt gradient distribution and carbonization activation process.

[0026] In this invention, pre-freezing is performed before freeze-drying under the conditions of -40℃ to -80℃ and a vacuum of 10 to 50 Pa. This is because freezing and vacuum sublimation bypass the liquid water stage, fundamentally avoiding the potassium salt redistribution and structural collapse caused by capillary contraction, osmotic water loss, and thermal demulsification during conventional heating and drying of the double emulsion. The pre-freezing temperature must be lower than the eutectic point of the inner and outer aqueous phases, ensuring that the water in both phases is completely frozen into ice crystals, thus "locking" the potassium salt in situ within the respective spatial positions of the emulsion droplets and preventing salt migration with the liquid water. Since high-concentration potassium salts significantly lower the freezing point, -40℃ is only a basic lower limit, while -80℃ ensures complete solidification of W2. The vacuum of 10 to 50 Pa is far lower than the triple point pressure of water (611). The sublimation of frozen ice into water vapor during heating, rather than through liquid water, leaves pores in situ after the ice crystals sublimate, while the potassium salt remains in its original position. The oil phase / carbon precursor framework does not shrink or collapse due to the absence of surface tension from liquid water, and the spatial structure of the W1 / O / W2 emulsion is completely preserved. This provides a structural basis for the subsequent coking-carbonization stage to achieve gradient activation of "potassium-rich outer layer and potassium-poor inner layer".

[0027] In this invention, the coking temperature is 400-450℃, and the time is 1-2 hours. Within this temperature range, the oil slurry undergoes a condensation reaction to form raw coke. If the temperature is below 400℃, the condensation reaction is incomplete, and the raw coke strength is insufficient; if the temperature is above 450℃, the raw coke structure is excessively dense, increasing the difficulty of subsequent activation. The coking process is carried out under an inert atmosphere (such as nitrogen or argon) to prevent oxygen from participating in the reaction and causing oxidation of the carbon materials.

[0028] In this invention, the carbonization temperature is 700-900℃, and the time is 1-4 h. Carbonization temperature is one of the key parameters of this process: below 700℃, the potassium salt activation reaction is insufficient, and the outer mesopores are underdeveloped; above 900℃, the carbon skeleton shrinks excessively, the specific surface area decreases, and the mesopore shell may collapse due to excessive etching. The carbonization time is 1-4 h; too short a time results in insufficient activation, while too long a time may cause micropores to expand into mesopores, reducing the microporosity. The carbonization process is carried out under a nitrogen atmosphere without the introduction of carbon dioxide or other oxidizing gases; the construction of the outer mesopores is achieved solely through the active species generated by the decomposition of the potassium salt itself.

[0029] In this invention, the carbonized sample is uniformly dispersed in a pure aqueous solution and acid-washed with an acid washing solution to obtain a mixed solution. The mixed solution is then filtered, washed with pure water, and dried at 100-150°C for 12-24 hours to obtain porous carbon. The acid washing solution is at least one of hydrochloric acid and sulfuric acid, and its concentration is 1 mol / L. The purpose of acid washing is to remove residual potassium salts and potassium-containing compounds generated in the reaction from the carbonized sample, ensuring the purity of the porous carbon.

[0030] In the following examples and comparative examples of this invention, the ethylene tar is Luqing ethylene tar, and the catalytic cracking slurry, vacuum residue, coking wax oil, and coal tar pitch are all slurries produced by our company. Potassium hydroxide, potassium acetate, potassium ethylenediaminetetraacetate, potassium stearate, and potassium tetraoxalate are sourced from commercially available sources, including Span series (such as Span 80), polyglycerol ricinoleate (PGPR), Tween series (such as Tween 80), and sodium dodecyl sulfate.

[0031] In this invention, the porous carbon obtained in the following examples and comparative examples was placed in a CVD furnace. All samples were subjected to the same CVD deposition conditions: heating to 500°C under argon protection, introducing a SiH4 / Ar mixture with a volume ratio of 1:10, deposition at atmospheric pressure, and a deposition time of 60 min for all samples. After deposition, the silane supply was stopped, and the samples were allowed to cool naturally to room temperature under an argon atmosphere to obtain silicon-carbon composite materials.

[0032] The obtained silicon-carbon composite material, conductive agent Super P, and binder CMC / SBR (CMC to SBR mass ratio 1:1) were mixed at a mass ratio of 80:10:10, and deionized water was added to form a uniform slurry. This slurry was then coated onto a copper foil current collector, vacuum dried at 120℃ for 12 h, rolled, and cut into 12 mm diameter electrode sheets. Subsequently, the sheets were transferred to an argon glove box to assemble CR2032 coin cells, using a lithium metal sheet as the counter electrode, a Celgard 2400 polypropylene microporous membrane as the separator, and a 1 mol / L LiPF6 / EC+DMC electrolyte (volume ratio 1:1). After standing for 8 h, the cells were tested.

[0033] Initial specific capacity and initial coulombic efficiency: Using a battery testing system, the battery was discharged at 0.05C to 0.005 V, then discharged at 0.01C to 0.005 V, and charged at 0.05C to 1.5 V. Initial coulombic efficiency = (initial charge capacity / initial discharge capacity) × 100%.

[0034] Cycling performance: After 500 cycles at 1C current density at room temperature, the capacity retention rate is calculated as (specific capacity after n-th delithiation / specific capacity after initial delithiation) × 100%.

[0035] Rate performance: Cycle 5 times each at 0.1C, 0.2C, 0.5C, 1C, 2C and 5C. 5C retention rate = 5C capacity / 0.1C capacity × 100%.

[0036] Volume expansion rate: The electrode thickness was measured before and after cycling using the electrode thickness method. Volume expansion rate = (thickness after cycling - thickness before cycling) / thickness before cycling × 100%.

[0037] Silicon content test: Weigh 50mg of silicon-carbon composite material into a crucible, place the crucible in a thermogravimetric analyzer, and heat it to 900℃ in an air atmosphere to oxidize carbon into CO2 and release it, and oxidize silicon into SiO2. Calculate the silicon content based on the residual mass, the initial mass, and the mass fraction of silicon in silicon dioxide.

[0038] Example 1 This embodiment uses catalytic cracking slurry as raw material.

[0039] Take 100 g of catalytic cracking slurry, add 4.0 g of Span 80 (HLB=4.3) as a lipophilic surfactant (accounting for 4 wt% of the slurry mass), stir for 30 min, and obtain the pretreated material.

[0040] Prepare a low-concentration potassium salt activator aqueous solution W1: a 5% potassium bicarbonate aqueous solution.

[0041] Prepare a high-concentration potassium salt activator aqueous solution W2: a 25% potassium bicarbonate aqueous solution, and add Tween 80 (HLB=15) as a hydrophilic surfactant at a concentration of 1.5 wt% of the mass of W2 (i.e., approximately 1.125 g of Tween 80 in 75 mL of W2), and stir until homogeneous.

[0042] Slowly add 12.5 mL of potassium salt activator aqueous solution W1 (the volume ratio of potassium salt activator aqueous solution W1 to oil slurry is 1:8) to the pretreated material, and stir at 1.5 × 10⁻⁶. 4 High-speed shearing at rpm for 10 min yields a W1 / O primary emulsion. The primary emulsion is then slowly added to 75 mL of the potassium salt activator aqueous solution W2 containing Tween 80 (W1 to W2 volume ratio 1:6), and the mixture is further sheared at 1.5 × 10⁻⁶ rpm for 10 min to form a W1 / O primary emulsion. 4 High-speed homogenization at rpm for 15 min resulted in a stable W1 / O / W2 type double emulsion.

[0043] Based on potassium salt solute, the mass of potassium salt in the potassium salt activator aqueous solution W1 is 12.5 × 0.05 = 0.625 g; the mass of potassium salt in the potassium salt activator aqueous solution W2 is 75 × 0.25 = 18.75 g; m2 / m1 = 30, the total amount of potassium salt added is m1 + m2 = 19.375 g, accounting for 19.375 wt% of the raw material oil slurry mass.

[0044] The resulting double emulsion was freeze-dried (pre-freezing temperature -60℃, vacuum degree 20 Pa) to obtain a carbon source precursor. Under a nitrogen atmosphere, it was coked at 420℃ for 1.5 h at a rate of 5℃ / min to obtain raw coke, which was then carbonized at 800℃ for 2 h at a rate of 5℃ / min to obtain a carbonized sample. Finally, it was acid-washed with 1 mol / L hydrochloric acid, washed with pure water until neutral, and dried at 120℃ for 18 h to obtain porous carbon.

[0045] After testing, Figure 1 Image (a) in the figure is a cross-sectional SEM image of the prepared green coke. Figure 1 (b) is the SEM image of the prepared green coke. Since the potassium salt content in the aqueous phase W1 is low, the potassium salt crystals dispersed inside the green coke are small. The potassium salt content in W2 is high, and agglomeration is easy to occur during coking. Therefore, the surface of the green coke is covered with abundant potassium salt block particles, forming a green coke structure with potassium-poor interior and potassium-rich exterior. Figure 2 (a) and Figure 2 (b) shows the scanning electron microscope images at low and high magnification, respectively. The porous carbon surface is relatively smooth and has no obvious macroporous structure. Figure 3 The image shows a TEM image of the porous carbon prepared in Example 1 of this invention. The light-colored edges represent the mesoporous shell, where the carbon skeleton is more etched, resulting in a lower density and greater electron beam penetration, thus displaying a lighter color. The dark-colored core represents the microporous core, where the original skeleton is less etched, maintaining a higher density and displaying a darker color. Figure 4 The XRD pattern of the raw coke prepared in Example 1 of this invention is shown in (002). The diffraction peaks exhibit a broad and short dome-shaped morphology, with diffuse peak shapes, indicating that the carbon matrix is ​​mainly composed of amorphous / randomized carbon structures with low orderliness in the carbon sheet stacking, which is beneficial for subsequent activation. Due to the high potassium salt content on the surface, the characteristic peaks of potassium salt in the XRD are sharp and have high intensity. The specific surface area of ​​the porous carbon obtained in this example is 1150 m². 2 / g, total pore volume is 0.65 cm³ 3 / g. The mesopore / micropore volume ratio is 0.48. This material exhibits a typical external mesopore-internal micropore gradient structure. When used as a CVD silicon-carbon anode support, the resulting composite material has a specific capacity of 1860 mAh / g, an initial coulombic efficiency of 86.8%, a capacity retention of 83% after 500 cycles, a capacity retention of 64% at 5C rate, and a volume expansion rate of 113%.

[0046] Example 2 The difference between this embodiment and Example 1 is as follows: the raw material oil slurry is replaced with ethylene tar; the lipophilic surfactant is replaced with polyglycerol ricinoleate (PGPR), and the addition amount is adjusted to 1.5 wt% of the oil slurry mass (i.e., 1.5 g of PGPR is added to 100 g of oil slurry); the potassium salt activator is replaced with potassium oxalate, with the aqueous phase mass fraction of potassium salt activator aqueous solution W1 being 8% and the aqueous phase mass fraction of potassium salt activator aqueous solution W2 being 30%, and Tween 80 (HLB=15) is added to potassium salt activator aqueous solution W2 at an addition amount of 2.0 wt% of the mass of potassium salt activator aqueous solution W2; the volume ratio of W1 to W2 is adjusted to 1:7, the volume ratio of potassium salt activator aqueous solution W1 to raw material oil slurry is 1:9, the total potassium salt addition amount is 24.23 wt%, and m2 / m1=26.25; the coking temperature is changed to 400℃, and the coking time is 2 h; the carbonization temperature is changed to 700℃, and the carbonization time is extended to 3 h. The remaining operations are the same as in Example 1.

[0047] The structure and properties of the porous carbon obtained in this embodiment are characterized as follows: The specific surface area of ​​the obtained porous carbon is 1080 m². 2 / g, total pore volume is 0.56 cm³ 3 The mesopore / micropore volume ratio is 0.28. Due to its slightly lower carbonization temperature, the development of the mesopore shell is slightly less than that in Example 1, but a complete gradient structure is still formed. When used as a CVD silicon-carbon anode support, the composite material has a specific capacity of 1830 mAh / g, an initial coulombic efficiency of 85.5%, a capacity retention of 81.5% after 500 cycles, and a capacity retention of 62% at 5C rate.

[0048] Example 3 The difference between this embodiment and Example 1 is as follows: the raw material is a mixture of catalytic cracking slurry and coal tar pitch in a 1:1 mass ratio. The lipophilic surfactant is a blend of Span 80 and PGPR (HLB≈4.0), added at 5 wt% of the slurry mass. W1 is a 10% potassium hydroxide aqueous solution, and W2 is a mixed aqueous solution formed by a blend of potassium hydroxide and potassium carbonate, wherein the total mass fraction of potassium hydroxide and potassium carbonate is 20%, and their molar ratio is 1:1. Sodium dodecyl sulfate (SDS, HLB=12) is added to W2 as a hydrophilic surfactant, added at 0.8 wt% of the W2 mass. The volume ratio of W1 to slurry is 1:10 (10 mL), and the volume ratio of W1 to W2 is 1:8 (W2=80 mL). The total potassium salt added is 1 + 16 = 17 g, accounting for 17 wt% of the slurry, with m2 / m1=16. The coking temperature is 450℃ for 1 h; the carbonization temperature is 900℃ for 1 h. The rest is the same as in Example 1.

[0049] The structure and properties of the porous carbon obtained in this embodiment are characterized as follows: The specific surface area of ​​the obtained porous carbon is 1200 m².2 / g, total pore volume is 0.72 cm³ 3 The mesopore / micropore volume ratio is 0.78. Due to the higher activator content and carbonization temperature, the mesopore shell is etched more thoroughly, resulting in an increased mesopore ratio. When used as a CVD silicon-carbon anode support, the composite material exhibits a specific capacity of 1920 mAh / g, an initial coulombic efficiency of 86.0%, a capacity retention of 81% after 500 cycles, and a capacity retention of 66% at 5C rate.

[0050] Example 4 The difference between this embodiment and Example 1 is as follows: the raw material is vacuum residue, and the lipophilic surfactant is Span 60 (HLB=4.7), added at 1 wt% of the oil slurry mass. W1 is a 6% potassium acetate aqueous solution, and W2 is a 22% potassium acetate aqueous solution. Tween 60 (HLB=14.9) is added to W2 at 3.0 wt% of its mass. The volume ratio of W1 to oil slurry is 1:7 (approximately 14.3 mL), and the volume ratio of W1 to W2 is 1:5 (W2=71.5 mL). The total potassium salt added is 0.858 + 15.73 = 16.59 g, accounting for 16.59 wt% of the oil slurry, with m2 / m1=18.3. The coking temperature is 410℃ for 1.8 h; the carbonization temperature is 750℃ for 2.5 h. Pickling is performed using 1 mol / L sulfuric acid, and drying is carried out at 100℃ for 24 h. The rest is the same as in Example 1.

[0051] The structure and properties of the porous carbon obtained in this embodiment are characterized as follows: The specific surface area of ​​the obtained porous carbon is 1020 m² / g. 2 / g, total pore volume is 0.52 cm³ 3 / g, with a mesoporous / microporous pore volume ratio of 0.22. When used as a CVD silicon-carbon anode support, the composite material has a specific capacity of 1810 mAh / g, an initial coulombic efficiency of 85.2%, a capacity retention of 80.5% after 500 cycles, and a capacity retention of 60.5% at 5C rate.

[0052] Example 5 The difference between this embodiment and Example 1 is that the raw material is a mixture of ethylene tar and coking wax oil (mass ratio 2:1), the lipophilic surfactant is Span 80 (HLB=4.3), and the amount added is 3.5 wt% of the oil slurry mass.

[0053] Prepare a low-concentration potassium salt activator aqueous solution W1: a 5% potassium tetraoxalate aqueous solution; prepare a high-concentration potassium salt activator aqueous solution W2: a 25% potassium tetraoxalate aqueous solution, and add Tween 80 (HLB=15) to W2 at a rate of 1.0 wt% of the mass of W2.

[0054] Slowly add 12.5 mL of W1 (W1 to oil slurry volume ratio of 1:8) to the pretreated material, at a concentration of 1.5 × 10⁻⁶. 4 High-speed shearing at rpm for 10 min yields a W1 / O primary emulsion; then 87.5 mL of W2 (W1 to W2 volume ratio 1:7) is slowly added, and the mixture is further sheared at 1.5 × 10⁻⁶ rpm for 10 min to form a W1 / O primary emulsion; 4 High-speed homogenization was performed at rpm for 15 min to form a stable W1 / O / W2 type double emulsion. The total potassium salt addition was 0.625 + 21.875 = 22.5 g, accounting for 22.5 wt% of the raw material oil slurry, with m2 / m1 = 35. The coking temperature was changed to 430℃, the carbonization temperature was changed to 850℃, and the remaining operations were the same as in Example 1.

[0055] The structure and properties of the porous carbon obtained in this embodiment are characterized as follows: The specific surface area of ​​the obtained porous carbon is 1160 m². 2 / g, total pore volume is 0.68 cm³ 3 The mesoporous / microporous pore volume ratio is 0.58. When used as a CVD silicon-carbon anode support, the composite material has a specific capacity of 1880 mAh / g, an initial coulombic efficiency of 86.2%, a capacity retention of 82.5% after 500 cycles, and a capacity retention of 64.5% at 5C rate.

[0056] Comparative Example 1 The difference between this comparative example and Example 1 is that a W1 / O / W2 type dual emulsion is not constructed. Instead, all potassium salts (total addition amount is the same as 19.375 g potassium bicarbonate in Example 1) are directly dissolved in deionized water. The amount of deionized water is determined according to the total water content of the potassium salt activator aqueous solutions W1 and W2 in Example 1, so that the total water content of this comparative example is consistent with that of Example 1. After mixing with oil slurry and surfactant, high-speed shearing is performed. Subsequent coking, carbonization, and pickling steps are the same as in Example 1. The amount of surfactant added is the same as in Example 1.

[0057] The structure and properties of the porous carbon obtained in this comparative example were characterized as follows: Due to the lack of a dual emulsion structure, the mixed liquid system obtained after high-speed shearing lacked stability and was prone to phase separation, resulting in uneven dispersion of potassium salts in the system. During coking, some potassium salts agglomerated to form large-sized grains, leading to an increase in the relative potassium salt content in local coking areas, enhanced etching, and easier formation of macropores, such as... Figure 5 As shown in (b); another portion of potassium salts has a lower degree of aggregation and weaker local etching effect. After reacting with the carbon framework, it can form micro and mesopores, resulting in a smoother porous carbon surface, such as... Figure 5 As shown in (a) above, the specific surface area of ​​the obtained carbon material is 650 m². 2 / g, total pore volume is 0.33 cm³ 3 / g. Due to the inability of the activator to achieve a spatial gradient distribution, the potassium salt is randomly distributed and activated within the carbon framework after carbonization, resulting in a disordered pore structure. The carbon material as a whole is dominated by micropores with a low proportion of mesopores, and the mesopore / micropore volume ratio is only 0.07. The activation is extremely uneven, and some parts are etched into ultra-large pores, or even the carbon framework is broken. When used as a CVD silicon-carbon anode support, the composite material has a specific capacity of 1500 mAh / g, an initial coulombic efficiency of only 78%, a capacity retention of 42% after 500 cycles, a capacity retention of <28% at 5C rate, and a volume expansion rate of 160%.

[0058] Comparative Example 2 The difference between this comparative example and Example 1 is that the volume ratio of W1 to W2 is adjusted to 1:9 (exceeding the upper limit of 1:8). Specifically, W1 = 10 mL (5%), W2 = 90 mL (25%), total potassium salt = 0.5 + 22.5 = 23 g, accounting for 23 wt%, m2 / m1 = 45. The other conditions are the same as in Example 1.

[0059] The structure and properties of the porous carbon obtained in this comparative example were characterized as follows: the specific surface area of ​​the obtained carbon material was tested to be 950 m². 2 / g, total pore volume is 0.74 cm³ 3 / g. Due to the excessive amount of potassium salt in the outer layer, the activation reaction was too vigorous, resulting in excessive etching and expansion of the outer layer, producing a large number of mesopores and some macropores (approximately 7%). The proportion of micropores decreased to 50.4%, and the proportion of mesopores was 42.6%, with a mesopore / micropore volume ratio as high as 0.85. Figure 6 As shown, the gradient structure is disrupted. When used as a CVD silicon-carbon anode support, the composite material exhibits an initial coulombic efficiency of only 76%, and a capacity retention of 58% after 500 cycles.

[0060] Comparative Example 3 The difference between this comparative example and Example 1 is that the volume ratio of W1 to W2 is adjusted to 1:4, which is lower than the 1:5 to 1:8 specified in this invention. Specifically, W1 is 12.5 mL of a 5% potassium bicarbonate aqueous solution, and W2 is 50 mL of a 5.32% potassium bicarbonate aqueous solution. The volume ratio of W1 to the oil slurry is 1:8. The total potassium salt added accounts for 3.3 wt% of the oil slurry, m2 / m1 = 4.26, and the remaining steps of oil slurry, surfactant, shearing, homogenization, freeze drying, coking, carbonization, and pickling are the same as in Example 1.

[0061] The structure and properties of the porous carbon obtained in this comparative example were characterized as follows: the specific surface area of ​​the obtained carbon material was tested to be 780 m². 2 / g, total pore volume is 0.38 cm³ 3 / g. Due to the low proportion and concentration of W2 in the external aqueous phase, the potassium enrichment of the outer layer of the raw coke is severely insufficient. During carbonization, there are few activation sites for the outer potassium salt, and the mesoporous shell is underdeveloped. The resulting porous carbon is still predominantly microporous, with a mesoporous / microporous pore volume ratio of 0.10. When used as a CVD silicon-carbon anode support, the composite material has a specific capacity of 1650 mAh / g, but at a 5C rate, the capacity retention is only 38%, and the volume expansion rate reaches 148%.

[0062] Comparative Example 4 The difference between this comparative example and Example 1 is that: W1 is 12.5 mL of a 5% potassium bicarbonate aqueous solution, W2 is 75 mL of a 5.83% potassium bicarbonate aqueous solution, the volume ratio of W1 to W2 is 1:6, and the volume ratio of W1 to the oil slurry is 1:8. The total amount of potassium bicarbonate added is adjusted to 5 wt% of the raw material oil slurry, m2 / m1=7, and the remaining steps of oil slurry, surfactant, shearing, homogenization, freeze drying, coking, carbonization, and pickling are the same as in Example 1.

[0063] The structure and properties of the porous carbon obtained in this comparative example were characterized as follows: the specific surface area of ​​the obtained carbon material was measured to be 820 m². 2 / g, total pore volume is 0.38 cm³ 3 / g. Due to insufficient activation sites in the outer potassium salt layer, the mesoporous shell is underdeveloped, with a mesopore ratio of only 11.2% and a mesopore / micropore volume ratio of 0.13, failing to form an effective mesoporous shell. When used as a CVD silicon-carbon anode support, the composite material has a specific capacity of 1660 mAh / g, but the capacity retention rate at 5C rate is only 40%, and the volume expansion rate reaches 152%.

[0064] Comparative Example 5 The difference between this comparative example and Example 1 is that W1 is 16.7 mL of a 10% potassium bicarbonate aqueous solution, and W2 is 113.3 mL of a 25% potassium bicarbonate aqueous solution. The volume ratio of W1 to W2 is approximately 1:6.8, and the volume ratio of W1 to the oil slurry is 1:6. The total amount of potassium bicarbonate added is adjusted to 30 wt% of the raw material oil slurry, m2 / m1 = 16.96. The remaining steps of oil slurry, surfactant, shearing, homogenization, freeze drying, coking, carbonization, and pickling are the same as in Example 1.

[0065] The structure and properties of the porous carbon obtained in this comparative example: The specific surface area of ​​the obtained carbon material was tested to be 980 m². 2 / g, total pore volume is 0.78 cm³ 3 / g. Due to the excessive gas generated by the decomposition of the activator, the mesopores excessively expand into macropores, and the mesopore / micropore volume ratio rises to 1.05, severely damaging the microporous nuclei in the gradient structure. When used as a CVD silicon-carbon anode support, the composite material's initial coulombic efficiency is only 75%, and the capacity retention rate is 55% after 500 cycles.

[0066] Comparative Example 6 The difference between this comparative example and Example 1 is that the carbonization temperature is changed to 600°C, while the rest of the operation is the same as in Example 1, and the amount of surfactant added is the same as in Example 1.

[0067] The structure and properties of the porous carbon obtained in this comparative example were characterized as follows: the specific surface area of ​​the obtained carbon material was tested to be 580 m². 2 / g, total pore volume is 0.25 cm³ 3 / g. Due to the excessively low carbonization temperature, the potassium salt activation reaction was insufficient, and almost no outer mesopores were formed, with a mesopore / micropore volume ratio of only 0.05. When used as a CVD silicon-carbon anode support, the composite material exhibited an initial coulombic efficiency of only 70%, a capacity retention of 50% after 500 cycles, and a capacity retention of <30% at 5C rate.

[0068] Comparative Example 7 The difference between this comparative example and Example 1 is that the carbonization temperature is changed to 950°C, while the rest of the operation is the same as in Example 1, and the amount of surfactant added is the same as in Example 1.

[0069] The structure and properties of the porous carbon obtained in this comparative example were characterized as follows: the specific surface area of ​​the obtained carbon material was tested to be 880 m². 2 / g, total pore volume is 0.58 cm³ 3 / g. Due to the excessively high carbonization temperature, the carbon skeleton undergoes excessive shrinkage and graphitization, resulting in a decrease in specific surface area; at the same time, the mesoporous shell partially collapses due to excessive etching, and the micropore ratio drops to 55%. When used as a CVD silicon-carbon anode support, the composite material has a specific capacity of only 1580 mAh / g and an initial coulombic efficiency of 80%.

[0070] The performance test data of Examples 1-5 and Comparative Examples 1-7 are shown in Table 1.

[0071] Table 1

Claims

1. A method for preparing porous carbon, characterized in that, Includes the following steps: 1) Add a lipophilic surfactant to the raw oil slurry, stir, and obtain the pretreated material; 2) Slowly add a 5%~10% potassium salt activator aqueous solution W1 to the pretreated material to form a W1 / O primary emulsion under high-speed shearing; 3) The W1 / O primary emulsion was added to an aqueous solution of potassium salt activator containing 20%~30% by mass of hydrophilic surfactant under stirring, and a stable W1 / O / W2 type double emulsion was formed by high-speed homogenization. 4) The W1 / O / W2 type dual emulsion was pre-frozen and then freeze-dried to obtain a carbon source precursor; 5) Under an inert atmosphere, coking-carbonization treatment is carried out to obtain carbonized samples; 6) The carbonized sample is sequentially acid-washed, water-washed, and dried to obtain a porous carbon product; In step 2), the rotational speed of the high-speed shear is 1.2 × 10⁻⁶. 4 ~2.0×10 4 rpm, time is 5~30 min; In step 3), the rotational speed for high-speed homogenization is 1.2 × 10⁻⁶. 4 ~2.0×10 4 rpm, time is 5~30 min.

2. The preparation method according to claim 1, characterized in that, The volume ratio of potassium salt activator aqueous solution W1 to potassium salt activator aqueous solution W2 is 1:5~1:8; The volume ratio of potassium salt activator aqueous solution W1 to raw material oil slurry is 1:10~1:

6.

3. The preparation method according to claim 2, characterized in that, In steps 2) and 3), based on potassium salt solute, the mass of potassium salt in the potassium salt activator aqueous solution W1, m1, is 0.5 wt% to 1.5 wt% of the raw material oil slurry mass, and the mass of potassium salt in the potassium salt activator aqueous solution W2, m2, is 10 wt% to 24 wt% of the raw material oil slurry mass; m2 / m1 is 10 to 40, and m1+m2 is 10 wt% to 25 wt% of the raw material oil slurry mass.

4. The preparation method according to claim 1, characterized in that, The potassium salt activator in steps 2) and 3) is selected from at least one of potassium hydroxide, potassium carbonate, potassium bicarbonate, potassium oxalate, potassium phosphate, potassium acetate, potassium citrate, potassium ethylenediaminetetraacetate, potassium stearate, and potassium tetraoxalate.

5. The preparation method according to claim 1, characterized in that, In step 1), the feedstock slurry is at least one of catalytic cracking slurry, vacuum residue, coking wax oil, ethylene tar, and coal tar pitch.

6. The preparation method according to claim 1, characterized in that, In step 1), the lipophilic surfactant is at least one of the Span series or polyglycerol ricinoleate, with a hydrophilic-lipophilic balance value of 3-6; the amount of lipophilic surfactant added is 1wt%~5wt% of the oil slurry mass. In step 3), the hydrophilic surfactant is at least one of the Tween series and sodium dodecyl sulfate, with a hydrophilic-lipophilic balance value (HLB) of 8 to 15; the amount of hydrophilic surfactant added is 0.5 wt% to 5 wt% of the mass of the potassium salt activator aqueous solution W2.

7. The preparation method according to claim 1, characterized in that, In step 4), the pre-freezing temperature is -40℃ to -80℃, and the vacuum degree is 10 to 50 Pa.

8. The preparation method according to claim 1, characterized in that, In step 5), the coking-carbonization process is as follows: the temperature is increased to 400~450℃ at a heating rate of 5℃ / min for 1~2 hours, and then the temperature is increased to 700~900℃ at a heating rate of 5℃ / min for 1~4 hours, and the entire process is carried out under an inert atmosphere. In step 6), the carbonized sample is uniformly dispersed in a pure aqueous solution and then acid-washed with an acid washing solution to obtain a mixed solution; The mixed solution was filtered, washed with pure water, and then dried at 100~150℃ for 12~24h to obtain porous carbon. The pickling solution is at least one of hydrochloric acid and sulfuric acid, and the concentration of the pickling solution is 1 mol / L.

9. Porous carbon prepared by the preparation method according to any one of claims 1-8, characterized in that, Porous carbon has a core-shell structure, with a core of micropores and a shell of mesopores, and a mesopore / micropore volume ratio of 0.2 to 0.

8. Porous carbon with a specific surface area ≥1000 m² 2 / g, total pore volume ≥0.5 cm³ 3 / g.

Citation Information

Patent Citations

  • Preparation method and application of petroleum coke based activated carbon with zinc oxide and aluminium oxide as templates

    CN103641114A

  • Method for preparing sulfur-enriched activated carbon by using high-sulfur petroleum coke

    CN105712347B